2014
DOI: 10.3109/10428194.2014.939964
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gemcitabine, oxaliplatin and L-asparaginase and etoposide, vincristine, doxorubicin, cyclophosphamide and prednisone as first-line chemotherapy in patients with stage IE to IIE extranodal natural killer/T-cell lymphoma: a multicenter retrospective study

Abstract: Optimal chemotherapy regimen for Extranodal natural killer/T-cell lymphoma (ENKTL) has not yet been defined. We retrospectively compared the outcome of 93 patients newly diagnosed with stage IE to IIE ENKTL who received gemcitabine, oxaliplatin and L-asparaginase (GELOX) (n = 40) or etoposide, vincristine, doxorubicin, cyclophosphamide and prednisone (EPOCH) (n = 53) as induction chemotherapy. After induction chemotherapy, the complete response (CR) rate and overall response rate (ORR) for the GELOX group were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Treatment should be individualized based on patient's tolerance and comorbidities. Retrospective comparative studies have shown that asparaginase-and pegaspargasebased regimens are associated with superior efficacy compared with conventional anthracycline-based regimens for the treatment of stage I-II disease, 50,51 with pegaspargase-based regimens preferred.…”
Section: Nccn Recommendationsmentioning
confidence: 99%
“…Treatment should be individualized based on patient's tolerance and comorbidities. Retrospective comparative studies have shown that asparaginase-and pegaspargasebased regimens are associated with superior efficacy compared with conventional anthracycline-based regimens for the treatment of stage I-II disease, 50,51 with pegaspargase-based regimens preferred.…”
Section: Nccn Recommendationsmentioning
confidence: 99%
“…In ENKTCL patients, anthracyclines-based chemotherapy, such as CHOP, result in poorer responses because of high MDR gene expression in tumor cells [21]. Our prospective study demonstrated that asparaginase-based chemotherapy (GELOX) improved the CR rate in early stage ENKTCL patients and resulted in longer PFS and OS [6]. However, 20%-30% of ENKTCL patients are resistant to asparaginase-based chemotherapy, and there are no known biomarkers for predicting response to asparaginase-based regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high rate of locoregional and systemic recurrence with standard radiotherapy treatment alone, chemotherapy has been integrated into the management of ENKTCL [4]. There is increasing evidence that asparaginase-based chemo-radiotherapy regimens are superior to anthracycline-based regimens in the treatment of ENKTCL due to overexpression of the multidrug-resistant (MDR) gene in tumor cells [5, 6]. Asparaginase-based chemotherapy combined with radiotherapy, which significantly improves long term survival rates, has therefore become the standard treatment for ENKTCL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Patients with advanced stage ENKTL received chemotherapy alone. The chemotherapy regimens were as follows: (1) EPOCH (etoposide, doxorubicin, vincristine, cyclophosphamide, prednisone); (2) GELOX (gemcitabine, oxaliplatin, L-asparaginase) [23]. Patients received at two to six cycles of initial chemotherapy.…”
Section: Treatment and Response Evaluationmentioning
confidence: 99%